The role of steroids in the prediction of affective disorders in adult men - Šrámková, Monika; Dušková, Michaela; Hill, Martin; Bičíková, Marie; Řípová, Daniela; Mohr, Pavel; Stárka, Luboslav (Steroids, 2017)
OBJECTIVE: Anxiety and mood disorders (AMD) are the most frequent mental disorders in the human population. They have recently shown increasing prevalence, and commonly disrupt personal and working lives. The aim of our study was to analyze the spectrum of circulating steroids in order to discover differences that could potentially be markers of affective depression or anxiety, and identify which steroids could be a predictive component for these diseases. METHODS: We studied the steroid metabolome including 47 analytes in 20 men with depression (group D), 20 men with anxiety (group AN) and 30 healthy controls. OPLS and multivariate regression models were used for statistical analysis. RESULTS: Discrimination of group D from controls by the OPLS method was absolute, as was group AN from controls (sensitivity=1.000 (0.839, 1.000), specificity=1.000 (0.887, 1.000)). Relatively good predictivity was also found for discrimination between group D from AN (sensitivity=0.850 (0.640, 0.948), specificity=0.900 (0.699, 0.972)). CONCLUSION: Selected circulating steroids, including those that are neuroactive and neuroprotective, can be useful tools for discriminating between these affective diseases in adult men.
Keywords: poruchy nálady; Humans; úzkost; Affective depression; Multivariate Analysis; Female; mladý dospělý; dospělí; lidé; Radioimmunoassay; radioimunoanalýza; pregnanolon; Anxiety; Mood Disorders; steroidy; Allopregnanolone; Adult; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; multivariační analýza; Male; Young Adult; Depression; Gas Chromatography-Mass Spectrometry; mužské pohlaví; Pregnanolone; Steroids; deprese; dehydroepiandrosteron; Dehydroepiandrosterone; Multivariate analysis